Tent encampments in Toronto, Canada: Excavating Northern housing informalities - Allison Evans (Radical Housing Journal, 2022)
This paper examines the ambiguities of municipal state regulation in relation to the dwelling practices of Toronto’s unhoused population. This paper argues tent encampments are a persistent mode of urban informality in the global North, where tents and other small structures provide a source of housing, particularly in cities with limited housing options. Using the City of Toronto as a case study, this paper analyzes how urban informality is reproduced and mediated by state policies, protocols, and actors. The findings suggest the local state—at times ambiguous and negotiated relative to an array of actors, property relations, and desirable formalities—routinely clears encampments from public property. The city’s enforcement and regulatory regime often removes tent encampments without rehousing people, thus contributing to cyclical patterns of informal urbanization. The paper concludes with recommendations for future research to better understand the similarities, differences, and nuances of this mode of urban informality in global North cities and to open the regulatory and policy field to options beyond criminalization.